Alkaline oxygen evolution: exploring synergy between fcc and hcp cobalt nanoparticles entrapped in N-doped graphene. (March 2022) - Singh, Ajit Kumar; Ji, Seulgi; Singh, Baghendra; Das, Chittaranjan; Choi, Heechae; Menezes, Prashanth W.; Indra, Arindam
Abstract: Herein, we report a Mott-Schottky catalyst by entrapping cobalt nanoparticles inside the N-doped graphene shell (Co@NC). The Co@NC delivered excellent oxygen evolution activity with an overpotential of merely 248 mV at a current density of 10 mA cm –2 with promising long-term stability. The importance of Co encapsulated in NC has further been demonstrated by synthesizing Co nanoparticles without NC shell. The synergy between the hexagonal close-packed ( hcp ) and face-centered cubic ( fcc ) Co plays a major role to improve the OER activity, whereas the NC shell optimizes the electronic structure, improves the electron conductivity, and offers a large number of active sites in Co@NC. The density functional theory calculations have revealed that the hcp Co has a dominant role in the surface reaction of electrocatalytic oxygen evolution, whereas the fcc phase induces the built-in electric field at the interfaces with N-doped graphene to accelerate the H + ion transport. Graphical abstract: A Mott-Schottky catalyst, Co encapsulated in N-doped graphene, has been demonstrated to be an excellent water oxidation electrocatalyst in comparison to co-nanoparticles. Image 1 Highlights: Facile synthesis of cobalt nanoparticles entrapped inside N-doped graphene shell (Co@NC). Superior alkaline water oxidation activity of Co@NC over Co nanoparticles. Synergy between fcc and hcp Co in Co@NC to improve water oxidation activity. hcp Co provides the active surface sites for electrocatalytic oxygen evolution.